The Influence of Combining Anti-Hypertension Exercise and Watermelon Juice on Blood Pressure Reduction in The Elderly Posyandu of Labruk Lor Village - Ridha Septrivinta; R. Endro Sulistyono; Iin Aini Isnawati (Health and Technology Journal (HTechJ), 2024)
The elderly are residents who have reached the age of 60 years or more. One of the diseases experienced by the elderly is hypertension. Hypertension is an increase in systolic blood pressure of at least 140 mmHg, and diastolic blood pressure of at least 90 mmHg. The management of hypertension is by pharmacology and non-pharmacology. One of non-pharmacological treatment by implementing the CERDIK program includes a diligent physical activity and a balanced diet. Antihypertensive exercise is an exercise that can increase the blood flow and oxygen supply to the heart muscle. The combination of drinking watermelon juice is done to prevent and reduce the hypertension. The purpose of this research is to determine the effect of antihypertensive exercise and watermelon juice on blood pressure in the elderly. This research used a quasi-experiment type of research with a pre-test – post-test approach with two group design. The samples of this study were 36 elderly with hypertension. The sampling technique used random sampling with a cluster sampling approach. The research instruments used modules and observations. The research was conducted from the 5th to the 19th of July 2024 at the elderly Posyandu in Labruk Lor Village, Lumajang District. Based on the results of the study, the average pre-test blood pressure value of the control and the experimental groups were almost entirely had hypertension. The research results showed that the average post-test blood pressure value of the control and intervention groups experienced a significant decrease. The results of the independent t test of the differences in blood pressure in the control and the experimental groups after being given antihypertensive exercise therapy and watermelon juice is by P value of 0.003 it can be concluded that there is a significant difference in elderly blood pressure between the control and experimental groups after being given therapy. The results of this study are expected to increase nurses’ knowledge about the effects of exercise and diet in the management of hypertension in order to provide effective education to patients.